Population structure of blue crab, portunus pelagicus (L.), in the Visayan sea implications to fisheries management - Romero, Filemon G.
The blue swimwear crab, Portumus pelagicus (L) supports the major marine crab fishery of the Philippines. It is the main target species for the crab meat processing industry and the 7th most important fishery export contributing to the national economy. However, there were indication of decline in catch between 1995-96 and the year of sampling, 2002-03. The density of fishermen was estimated to be about 11 fishermen per kilometer of coastline which is an indication of high fishing pressure. For this study, the mean CPUE for crab pots was highest in October at 0.012 kg/pot-hr and lowest (0.006 kg/pot-hr) in June. The CPUE for gill nets was highest at 0.15 kg/segment-hr in July and August and lowest in April 0.06 kg/segment-hr. There was no significant difference in CPUE across sites but there wre significant interactions between CPUE and season (ANOVA, α < 0.05). The size range of crabs was 6.0 to 18.5 cm CW. The mean size of crabs caught by crab pots ranged from 10.61 to 14.3 cm CW while for gill nets the range was 11.41 to 13.1 cm CW. The size frequency distribution showed that majority of the crabs caught were above the size at sexual maturity. Overall, the ratio between males and female was close to 1:1. However, for crab pots, females outnumbered the males. The population growth rate of P. pelagicus was estimated using the von Bertalanffy Growth equation and this showed that males grew faster than females. The estimates of L∞, was determined through the routines in ELEFANI and this ranged from 18.9 to 19.95 while the growth constant K ranged from 0.58 to 1.4 for the landed catch from different sampling sties. Estimated total morality (Z) ranged from 2.147 yr-1 to 5.285 yr-1. When all the carapace width frequency data from all samples for the four sites were pooled, treating the entire Visayan Sea as one fishing ground, Z was estimated to be 3.095 yr-1, natural morality Recruitment patterns into the fishery showed two major pulses, one higher than the other. Given that the peak in the incidence of egg-bearing females was in February and March and that larvae will recruit into the fishery after 8 to 9 months based on the larval duration and estimated age at size (CW), the major recruitment pulse in the fishery would be in October to November. These months coincided with the months with the highest CPUE which suggests that the spawning resulted to local recruitment. The other peak of incidence of egg-bearing females for the three sites was in October and November and recruitment into the fishery for the batch of larvae would be sometime in August. However for all these sites, this corresponded with months of low CPUE. This suggests that larvae spawned in October or November may not recruit locally. The fecundity of P. pelagicus in the Visayan Sea was comparable to other sites in the Philippines and int conformed with published works that fecundity increases with carapace width. The index of Reproductive Potential (IRP) was highest in Baud and Igbon (760), followed by Nabulwang (573) and Pasyagon (456.Overall, female crabs 12.5 to 14.5 cm CW have the highest potential reproductive output relative to other 48.6% in Igbon, 42.4% inBaud, 58.4% in Nabulwang and 54.7% in Pasyagon. Genetic analysis showed that the population of the crabs in the Visayan Sea had genetic affinities with that of Bohol but not with Tawi-Tawi. There was no significant genetic structuring among the sites in the Visayan Sea species in the Visayan Sea belongs to one stock. This concurs with results of the larval dispersal modeling which indicate larval exchange within the Visayan Sea during different monsoon periods. While Ighon and Baud have higher IRP, the larval dispersal model showed that a higher percentage of the particles (simulating larvae) from these sites were advected out of the Visayan Sea in April and November with some retention in May and August. In contrast, while the IRP of crab population un Nabulwang was lower, majority of particles released from this site were entrained within the Visayan Sea particularly in Asid Guld during different monsoon periods. Furthermore, results whos that the fishery in the Visayan Sea is replenished by local populations and these populations are likewise important sources of blue crab larva for areas outside the Visayan Sea.A Ecosystems-Based Approach for Fisheries Management for the Visayan Sea, treated as on fishery management unit, is recommended. A suite of management options to respond to each of the problems of the fishery have been recommended. A Multi-Criteria Analysis tool was formulated using biological/ecological, social and economic indicators to score each option according to the relative degree of impact, either positive or negative. From the initial scoring, the shift from gill nets to crab pots appears to be a better management option.